Heuristic algorithm to solve the short term transmission network expansion planning - Rider, Marcos J.; Gallego, Luis A. [UNESP]; Romero, Ruben [UNESP]; Garcia, Ariovaldo V.; IEEE (Ieee, 2007)
In this paper, a method for solving the short term transmission network expansion planning problem is presented. This is a very complex mixed integer nonlinear programming problem that presents a combinatorial explosion in the search space. In order to find a solution of excellent quality for this problem, a constructive heuristic algorithm is presented in this paper. In each step of the algorithm, a sensitivity index is used to add a circuit (transmission line or transformer) or a capacitor bank (fixed or variable) to the system. This sensitivity index is obtained solving the problem considering the numbers of circuits and capacitors banks to be added (relaxed problem), as continuous variables. The relaxed problem is a large and complex nonlinear programming and was solved through a higher order interior point method. The paper shows results of several tests that were performed using three well-known electric energy systems in order to show the possibility and the advantages of using the AC model.
Keywords: transmission network expansion planning; AC model; constructive heuristic algorithms; mixed integer nonlinear programming